The new Brazilian conservatism: Mapping its lines of force - Teixeira, Pedro Pinheiro; Henriques, Adrian (Education Policy Analysis Archives, 2022)
In the last decade, demands for greater order and the defense of traditional moral values have grown in Brazil, within the scope of what authors have been calling the new Brazilian conservatism. Conservative and neoliberal leaders and religious groups stand out, acting on different front lines in politics and social relations, including education. From this context, the article aims to map the different manifestations, actions and agents of the new Brazilian conservatism in the educational field, through theoretical reflection and the construction of a conceptual map. Initially, we discuss different conservative currents, especially the new conservatism in the USA and its influences in Brazil. From Almeida (2017), we outline a conceptual map of the new conservatism in education, highlighting four lines of force: moral, economic, security and socially intolerant. They have connections among themselves and are articulated according to the interests of their defenders. On the educational front, they propagate a technical, banking and authoritarian vision of education, emphasizing the role of the family, restricting teachers’ work and student autonomy. We conclude that these multiple lines of force lead to significant setbacks in the construction of plural educational proposals, affecting pedagogical practice, curricula and teacher education.